Enhancing 5G antenna performance by using 3D FSS structures. Issue 8 (5th May 2021) - Guidoum, Ferial; Tounsi, Mohamed Lamine; Vuong, Tan‐Phu; Ababou, Noureddine; Yagoub, Mustapha C.E.
Abstract: In this work, an enhanced 3D frequency selective surface (FSS) patch antenna is proposed for 5G applications. A 23 to 26 GHz patch antenna was first designed before improving its performance by adding a 3 × 5 unit cell two‐layer 2D transmission FSS structure. Then, reflective walls were placed on the side edges of the obtained structure in order to focus the incident field towards the main lobe; the aim being to build a 3D FSS structure without requiring the 3D printing technique. The total size of the obtained antenna is of 40 × 40 × 14 mm 3 . A comparative study was carried out between the performances of the patch antenna, the 2D FSS antenna and the 3D FSS antenna. A good agreement was observed between simulated results and measurements. An improvement of almost 3 and 2 dBi was obtained compared to the 2D FSS case, respectively, in simulated and measured results, while the side lobes in radiation patterns were decreased by more than 4 dBi, which confirms the adequate proposed design in switching to 3D structures.